Shame and Disavowing Queer Reality: An Autotheoretical Analysis - Forrest, Michelle; Joy, Phillip (Art/Research International)

(untitled) (University of Alberta, 2023)
Stigma has been defined as a spoiled identity, a branding that sets a person outside the norm, with potential to elicit feelings of shame. The authors recount firsthand experiences of having felt shame in connection with their queer identities and the disavowal this provoked, until such time as they met serendipitously as researchers with related interests and began sharing memories of being queer in a cis-heteronormative society. Two stories, illustrated in comic form and told in first-person narrative, are centrepieces for analysis in which the authors write against themselves, their past assumptions, and interpretations. Applying insights from queer and feminist decolonial theory, and from arts pedagogy, this autotheoretical analysis demonstrates that, despite the injurious nature of shame, revisiting and recodifying its roots can help one avow queer reality and come to terms with feelings of inadequacy induced by the politics of purity infecting many fledgling efforts at self-expression.